Analisis Kualitas Pelayanan Kesehatan Puskesmas Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan dengan Menggunakan Analisis Faktor - Elfemi Syafitri; Helma Helma (UNIVERSITAS NEGERI PADANG, 2020)
Abstract–Services are the activities of a person, to serve the process of fulfilling the needs of both directly and indirectly. The aim of this research is to find out how the quality of Inderapura Public Health Center health services. The type of the research used in this study is applied research and uses primary data which are gotten from the results of filling out the questionnaires. The population in this study were all residents of Inderapura Pancung Soal Subdistrict of 26,495 people with 100 samples. The sampling technique used is Non Probability Sampling, by means of Accidental Sampling. The results of the study were measured using 5 dimensions of public service quality namely: direct evidence, reliability, responsiveness, assurance and empathy. Based on the five variables used, the health services that provided by Inderapura Public Health Center staff were seen from the highest level of respondents feeling satisfied in Inderapura Public Health Center health services. This is shown from the results of the description of the study which is at 93.1%. The quality of the health service can be caused by internal and external factors Keywords–Service Quality, Puskesmas, Accidental Sampling, Factor Analysis.